2009
DOI: 10.1007/s10144-009-0168-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability, body characteristics and reproductive parameters of neighbouring rural and urban common kestrel (Falco tinnuculus) populations

Abstract: We tested the genetic and ecological differences between neighbouring urban and rural populations of common kestrels (Falco tinnuculus) in southern Bohemia. The aims were to (1) assess the genetic variability of the studied kestrel populations using microsatellite markers, (2) check the genetic relatedness of individuals within the urbanization gradient, and (3) compare possible gradients of body characteristics and reproductive parameters on the urbanization gradient. The mean expected allelic polymorphism di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…There were negative responses to urbanisation from Barn Owls, Eagle Owls, Eurasian Kestrels and Long-legged Buzzards with respect to urban-gradients (Bionda and Brambilla 2012;Dermerdzhiev et al 2014: Hindmarch . Although, in other urban-gradient studies, there appeared to be no effect of urbanisation on the number of young to fledge in Barn Owls and Eurasian Kestrels (Riegert et al 2010;Frey et al 2011).…”
Section: Number Of Young To Fledgementioning
confidence: 70%
See 3 more Smart Citations
“…There were negative responses to urbanisation from Barn Owls, Eagle Owls, Eurasian Kestrels and Long-legged Buzzards with respect to urban-gradients (Bionda and Brambilla 2012;Dermerdzhiev et al 2014: Hindmarch . Although, in other urban-gradient studies, there appeared to be no effect of urbanisation on the number of young to fledge in Barn Owls and Eurasian Kestrels (Riegert et al 2010;Frey et al 2011).…”
Section: Number Of Young To Fledgementioning
confidence: 70%
“…2; Salvati 2002; Kübler et al 2005;Carrillo and González-Dávila 2009;Costantini et al 2014) and were also negatively affected by urban cover in an urban gradient study in Austria (Sumasgutner et al 2014b). Conversely, another urban gradient study on Eurasian Kestrels in the Czech Republic showed no apparent effect of urbanisation (Riegert et al 2010), a finding also shown in Barn Owls (Frey et al 2011;Hindmarch et al 2014).…”
Section: Clutch Sizementioning
confidence: 86%
See 2 more Smart Citations
“…artificial stick nests, nest boxes) attached to tree trunks, fences, walls, utility poles, or posts. This is also the case for secondary cavity-nesting members of the Falconiformes and Strigiformes orders (Village 1983;Korpimäki 1984;Toland and Elder 1987;Schö nn et al 1991;Bortolotti 1994;Doody 1994;Gehlbach 1994a, b;Pomarol 1996;Valkama and Korpimäki 1999;Sullivan et al 2003;Franco et al 2005;Beasley and Parrish 2009;Steenhof and Peterson 2009;Charter et al 2007;van Nieuwenhuyse et al 2008;Costantini et al 2009;Ló pez et al 2010;Riegert et al 2010). Nest boxes are artificial cavities that have been designed to attract secondary cavity-nesters for roosting or breeding.…”
Section: Introductionmentioning
confidence: 99%